Electrospinning fabricated novel poly (ethylene glycol)/graphene oxide composite phase-change nano-fibers with good shape stability for thermal regulation. (August 2021) - Ji, Rong; Zhang, Qingfeng; Zhou, Fuxi; Xu, Fen; Wang, Xiaodong; Huang, Chaowei; Zhu, Yucao; Zhang, Huanzhi; Sun, Lixian; Xia, Yongpeng; Lin, Xiangcheng; Peng, Hongliang; et al.
Highlights: Novel PEG/GO composite phase-change nano-fibers were fabricated via electrospinning. The nanofibers exhibit a fine nano-fiber structure with GO on the surface. The nanofibers achieve a high latent heat capacity with good thermal reliability. The nano-fibers show a significant increase in thermal conductivity enhanced by GO. The nano-fibers exhibit excellent shape stability and thermal-regulated performance. Abstract: In this study, novel poly (ethylene glycol)/graphene oxide (PEG/GO) composite phase-change fibers (PCFs) were developed by using PEG as the phase change ingredient, GO as the thermally conductive filler, and PVP as the fiber matrix through electrospinning to enhance the thermal properties of shape-stabilized PCFs. Results indicated that PEG was grafted with GO by self-assembly among the functional groups. PVP was dispersed in the mixture to ensure nano-fiber formation. Transmission electron microscopy (TEM) and scanning electron microscopy (SEM) images revealed that the diameters of the composite PCFs decreased due to GO addition. The addition amount of GO is 0.5 wt% can prepare the composite PCFs with a homogeneous and smooth surface. DSC results demonstrated that the composite PCMs possess good phase-change behavior, fast thermal-response rates, and excellent thermal reliability. The largest melting/crystallization enthalpy of the prepared composite PCFs with 0.5 wt% GO addition was 103.6 J g −1 and 101.1 J g −1 . More importantly, after 100 DSC thermal cycles, there was no obvious change for phase-change enthalpy. The thermal conductivity of the composite PCFs can reach 0.5668 W/(m·K), indicating the thermal conductivity of composite PCFs increased significantly with the GO addition. Moreover, the composite PCFs possess excellent thermal-regulated performance, leakage resistance, and shape stability. Hence, the fabricated composite PCFs possess good comprehensive properties that can be used widely in thermo-regulated systems.